Territorios de investigación - Curtis, William J. R. (2003)
Comentarios acerca de las nuevas generaciones de arquitectos: <Abalos & Herreros>, <Mansilla + Tuñón Arquitectos>, <Foreign Office Architects>, <Díaz Moreno-García Grinda>, E. Arroyo, <NO.MAD Arquitectos, S.L.>, <Soriano-Palacios>, M. Ocaña, <Acebo-Alonso>, A. Payá, L. Alonso, J.García-Solera, J.D. Santos, <Nieto Sobejano Arquitectos>, <RCR Arquitectes>
Keywords: MOUSSAVI, FARSHID; DÍAZ MORENO, CRISTINA; GARCÍA GRINDA, EFRÉN; ARROYO, EDUARDO; SORIANO, FEDERICO; PALACIOS, DOLORES; OCAÑA, MANUEL; ACEBO, VICTORIA; ALONSO, ÁNGEL; GARCÍA-SOLERA, JAVIER; PAYÁ BENEDICTO, ALFREDO; ALONSO VERA, M. DOLORES; SANTOS, JUAN DOMINGO; CERO9; ARQUITECTURA; TEORIA; CRITICA; ESPAÑA; ÁBALOS, IÑAKI; HERREROS, JUAN; MANSILLA, LUIS MORENO; TUÑON, EMILIO; ARANDA, RAFAEL; PIGEM BARCELÓ, CARME; VILALTA PUJOL, RAMÓN; NIETO, FUENSANTA; SOBEJANO, ENRIQUE; ZAERA, ALEJANDRO